Pengaruh Media Penyiaran Pada Sistem Kognitif dan Sistem Afektif Khalayak - Prima Dona Hapsari (Rekam: Jurnal Fotografi, Televisi, Animasi)
The broadcasting media through radio and television broadcasts have influenced significantly on people’s views of its function as a medium toboost the popularity, propaganda, and image of a specific community. The broadcasting media have been able to bring a significant impact on its success in conveying the message to the audience. A two-way communication process between the communicant and communicatorshas been underlying such success as stated in the SR theory in which the media present great stimuli that are uniformly observed by the masses, and give more encouragement. This paper focuses on affective and cognitive aspects of the public affected by the broadcasting media. Radio and television audiences have known and understood certain information of which broadcasting media have already instilled that sense of understanding. Then, by knowing this tendency, they may arouse cognitive aspects to the audiences. In addition, the affective aspects caused by the broadcasting media have created the impression of empathy towardssomeone, and care about the launched programs. Therefore, it is expected that the broadcasting media really emphasize on educating function in which they are also able to educateand encourage audiences to be intelligent and critical audiences.Keywords: broadcasting media, communication, cognitive aspects, and affective aspects.